Liver fibrosis indices predict malignant cerebral edema after endovascular therapy for anterior circulation large vessel occlusion stroke: a retrospective cohort study - Weiwei Gao; Weiwei Gao; Weiwei Gao; Yanan Zhao; Jingjing She; Jingjing She; Jingjing She; Jingjing She; Ziwei Wu; Lijuan Cai; Lijuan Cai; Lijuan Cai; et al. (Frontiers in Neurology)
ObjectiveTo investigate the association between liver fibrosis indices and malignant cerebral edema (MCE) following endovascular therapy (EVT) for anterior circulation large vessel occlusion (LVO) stroke.MethodsThis single-center, retrospective cohort study consecutively enrolled 340 anterior circulation LVO stroke patients who underwent EVT between January 2018 and December 2024. The primary outcome was MCE, defined as a midline shift >5 mm at the level of the septum pellucidum or pineal gland, accompanied by the disappearance of the perimesencephalic cistern or the need for decompressive craniectomy. Multivariable logistic regression models were used to assess the independent associations of eight liver fibrosis indices with MCE, and restricted cubic spline regression analysis (RCS) was employed to explore their nonlinear relationships. The predictive performance was evaluated using receiver operating characteristic curves.ResultsMCE occurred in 69 patients (20.3%). After adjusting for multiple confounders, elevated fibrosis-4 index (FIB-4) (OR = 1.41, 95% CI: 1.09–1.82), modified FIB-4 (OR = 1.14, 95% CI: 1.05–1.23), aspartate aminotransferase (AST)/alanine aminotransferase (ALT) ratio (ARR) (OR = 2.35, 95% CI: 1.57–3.52), and AST/ALT-platelet ratio index (AARPRI) (OR = 2.63, 95% CI: 1.69–4.10) were independently associated with an increased risk of MCE, while FIB-5 index showed a negative association (OR = 0.89, 95% CI: 0.83–0.94). These liver fibrosis indices demonstrated moderate predictive performance (AUC: 0.65–0.68). RCS analysis revealed that most liver fibrosis indices exhibited an overall increasing dose–response relationship with MCE risk (both P-overall<0.05).ConclusionNon-invasive liver fibrosis indices could serve as novel biomarkers for risk stratification of MCE following EVT for stroke. These readily available tools may help identify high-risk patients who might benefit from early preventive interventions.